Supervision and professional development in social work practice - Nickson, Amanda M.; Anne Carter, Margaret; Francis, Abraham P. (NewDelhi : Sage publications, 2020)
This book highlights the uniqueness of supervision and its crucial role in developing competent social workers.
Foreword by Lambert K. Engelbrecht Preface Acknowledgments Introduction to Supervision: Concepts, Contexts and Issues Supervision in Social Work Theoretical Perspectives in Supervision Models of Supervision Strength-based Approaches to Supervision in Social Work Professional Development for Growth How to Work with Diversity in Supervision Challenges and Opportunities in Supervision: Examples from Multiple Practice Contexts Use of Technology in Supervision Practice of Compassion in Supervision Reflective Supervision and Building Resilience Making the Most of Supervision: Quality Matters Appendices Index.
Keywords: Social service Practice; Career development